2023
DOI: 10.3390/genes14112072
|View full text |Cite
|
Sign up to set email alerts
|

Role of Different Members of the AGPAT Gene Family in Milk Fat Synthesis in Bubalus bubalis

Zhipeng Li,
Ruijia Li,
Honghe Ren
et al.

Abstract: During triacylglycerol synthesis, the acylglycerol-3-phosphate acyltransferase (AGPAT) family catalyzes the conversion of lysophosphatidic acid to phosphatidic acid and the acylation of sn-2 fatty acids. However, the catalytic activity of different AGPAT members is different. Therefore, this study aimed to investigate the mechanism through which different AGPATs affect the efficiency of TAG synthesis and fatty acid composition. The conservation of amino acid sequences and protein domains of the AGPAT family wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(63 reference statements)
0
0
0
Order By: Relevance
“…Triacylglycerol (TAG), which comprises 98% of the fat in buffalo milk, is synthesized from fatty acids and glycerin by enzymes such as GPAT, AGPAT, LPIN, and DGAT [ 32 ]. Among them, GPAM catalyzes glycerol-3-phosphate to produce lysophosphatidic acid, AGPAT catalyzes the conversion of LPA to phosphatidic acid, then further dephosphorylates it to form DAG, and then catalyzes it with DGAT to produce triglyceride [ 16 ]. In this study, we found that after PPARγ-X17 overexpression, the expression of ACSL1 , CD36 , and GPAM was significantly increased, while the expression of ACACA was found to be significantly decreased ( Figure 6 ), suggesting that PPARγ-X17 overexpression can regulate fatty acid transport and triglyceride synthesis but does not affect the de novo synthesis of fatty acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triacylglycerol (TAG), which comprises 98% of the fat in buffalo milk, is synthesized from fatty acids and glycerin by enzymes such as GPAT, AGPAT, LPIN, and DGAT [ 32 ]. Among them, GPAM catalyzes glycerol-3-phosphate to produce lysophosphatidic acid, AGPAT catalyzes the conversion of LPA to phosphatidic acid, then further dephosphorylates it to form DAG, and then catalyzes it with DGAT to produce triglyceride [ 16 ]. In this study, we found that after PPARγ-X17 overexpression, the expression of ACSL1 , CD36 , and GPAM was significantly increased, while the expression of ACACA was found to be significantly decreased ( Figure 6 ), suggesting that PPARγ-X17 overexpression can regulate fatty acid transport and triglyceride synthesis but does not affect the de novo synthesis of fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristic analysis of the PPARG isoforms was performed referring to the previous reports [ 15 , 16 ]. In brief, a neighbor-joining phylogenetic tree was constructed in MEGA11 (v11.0.11).…”
Section: Methodsmentioning
confidence: 99%
“…ACADS , AGPAT4 , PTDSS2 , and SMOX are mainly involved in lipid metabolism and amino acid metabolism pathways. ACADS is involved in the fatty acid metabolism pathway ( 47 ), AGPAT4 promotes triacylglycerol synthesis and fatty acid composition ( 48 ), PTDSS2 is involved in the glycerophospholipid metabolism pathway ( 49 ), and SMOX is a candidate gene for growth, carcass composition traits, and milk production traits ( 50 , 51 ). In addition, previously reported traits associated with immunity ( BPIFA3 , LRRC66 ) ( 52 , 53 ), coat color ( ASIP ) ( 54 ), milk composition ( CSN1S1 , DGAT2 , PLIN4 , PLIN5 , IGF2R ) ( 55 ), and milk production ( AMPD1 ) ( 56 ) were also found in imported breeds.…”
Section: Discussionmentioning
confidence: 99%